Comparison of anthropometric measurements related to the medial longitudinal arch of feet between non-dancers and Bharatnatyam dancers- an observational study - Shwetha Acharya; Chandni Gupta; Vikram Palimar; Sneha Guruprasad Kalthur; Vaishali Yagain (Translational Research in Anatomy)
Background: Bharatnatyam is an Indian classical dance form that involves rhythmic barefoot tapping at varying speeds. The intense impact forces generated during this dance can result in biochemical alterations in the feet, potentially causing injuries to ligaments, tendons, and fascia. This can lead to changes in the structure of the foot over time. Therefore, this study was conducted to compare anthropometric measurements related to the medial longitudinal arch of the foot in non-dancer, mid-stage, and last stage Bharatnatyam dancers. Methods: The study was conducted on 192 participants. They were divided into three groups: 1) Non dancers 2) Mid-stage Bharatnatyam dancers, and 3) Last-stage Bharatnatyam dancers. Each group consisted of 64 participants each. Various measurements were taken on both the right and left foot using a wooden platform, foot image, and footprint. Later the results were analyzed statistically. Results: On comparing the parameters in non-dancers and mid-stage Bharatnatyam dancers it was found that all the parameters were found to be significant except right and left arch index. On comparing the parameters of mid-stage and last-stage Bharatnatyam dancers, it was found that none of the parameters showed significant value. On comparing the non-dancers and last-stage Bharatnatyam dancers, it was found that except right and left arch index all the parameters were found to be significant. Conclusion: From the results of the present study, it can be concluded that there were significant changes in the arches of the foot between the non-dancers and mid-stage and last-stage Bharatnatyam dancers.